2014
DOI: 10.1016/s2214-109x(14)70276-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health-system strengthening on under-5, infant, and neonatal mortality: 11-year provincial-level time-series analyses in Mozambique

Abstract: SummaryBackgroundKnowledge of the relation between health-system factors and child mortality could help to inform health policy in low-income and middle-income countries. We aimed to quantify modifiable health-system factors and their relation with provincial-level heterogeneity in under-5, infant, and neonatal mortality over time in Mozambique.MethodsUsing Demographic and Health Survey (2003 and 2011) and Multiple Indicator Cluster Survey (2008) data, we generated provincial-level time-series of child mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…Whereas initiatives to reduce neonatal mortality in the community are being implemented, a concurrent scaling up of care in the health facilities where referrals of difficult cases are envisaged is not taking place. Improvement in public health systems has been highlighted as a necessary component to achieving reduction in neonatal and under 5 mortality [16][17][18] . Majority of deaths (52%) occurred within the first 24 hours, this finding is similar to that observed in neonatal units in other developing countries 3,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas initiatives to reduce neonatal mortality in the community are being implemented, a concurrent scaling up of care in the health facilities where referrals of difficult cases are envisaged is not taking place. Improvement in public health systems has been highlighted as a necessary component to achieving reduction in neonatal and under 5 mortality [16][17][18] . Majority of deaths (52%) occurred within the first 24 hours, this finding is similar to that observed in neonatal units in other developing countries 3,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study on epidemiological data supporting the new concept of the post-newborn period. Infant mortality has gradually dropped down with an obvious imbalance in different countries and areas (24)(25)(26). Neonatal mortality in the United States in 2006 has dropped by nearly half as compared with that in 1980 (from 8.48% to 4.45%) (27), whereas it has decreased by 70% in China in 2008 as compared with that in 1990 (from 34.0% to 10.2%) (28).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal mortality in the United States in 2006 has dropped by nearly half as compared with that in 1980 (from 8.48% to 4.45%) (27), whereas it has decreased by 70% in China in 2008 as compared with that in 1990 (from 34.0% to 10.2%) (28). A study referring to 11-year provincial-level time-series analyses in Mozambique showed that neonatal mortality in different provinces ranged from 13.6% to 4.2%, and the differences might be most strongly associated with institutional birth attendance, maternal and child nurse density and overall health workforce density (26). Infant mortality in developed areas including North America and Europe in 2002 dropped by half as compared with that in 1990 (from 14% to 7%), whereas it only dropped from 75% to 61% in developing areas.…”
Section: Discussionmentioning
confidence: 99%
“…22 Multiple studies in other settings suggest that national health gains can often mask substantial heterogeneity in health system performance and outcomes. 23,24 In many settings, impoverished and/or geographically inaccessible areas have experienced slower progress in achieving health goals. 25,26 In other studies, socioeconomic status did not correlate well with health system performance.…”
Section: Discussionmentioning
confidence: 99%